TREATMENT AND RESOLVING SEVERE, POTENTIAL LIFE-THREATENING COMPLICATIONS (PNEUMOMEDIASTNUM, PNEUAMTOCELES, PULMONARY FIBROSIS ) IN COVID-19 PATIENT-CASE REPORT - Stojkovikj, Jagoda (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
SARS-CoV-2 sometime is associated with potential life-threatening rare complication, more specifically, pneumomediastinum, pneumatocelÐµs, cyst formations, and very often pulmonary fibrosis.  Our patient was 35 years old with main complaints: dry cough. chest pain, fatigue. She experienced a severe form of COVID 19, which resulted in complications of pneumomediastinum, pneumatocell, and pulmonary fibrosis. During the treatment of six months there is an almost complete withdrawal of the complications. She now feels well, able to work, and is still under our control. Physicians should be aware and careful in COVID 19 patients with severe clinical form given ventilator support, that such complications are possible and before a discharge from the hospital to do an X-ray or CT scan of the lungs. Especially when advising procedures such as postural drainage. Key words : COVID19, pneumomediastinum, pneumatocella, pulmonary fibrosis https://doi.org/10.55302/JMS2143138s